REVIEW PAPER ON BABY INCUBATOR - Miss. Potdar M. D; Miss. Bansode T. R. (International Engineering Journal For Research & Development, 2022)
Infants who born before 37 weeks of the gestation period are known as preterm or premature babies. Preterm baby requires surrounding exactly similar as in the womb to cope with the external environment. In fact mammals have the advantage of being homoeothermic, i.e. they have a nearly uniform body temperature, regulated independent of the environmental temperature. Babies born prematurely may need additional time to develop their lungs and other vital organs. (Their eyes and ear drums may be so sensitive that normal light and sound would cause permanent damage to these organs.) Also, babies born extremely early will not have had the time to develop fat just under the skin and will need help to keep themselves warm and toasty. Sometimes babies will have fluid or meconium in their lungs. This can lead to infections and an inability to breathe well. New-born may also have immature, not fully developed lungs that require monitoring and extra oxygen. An infant has a relatively large surface area, poor thermal insulation, and a small amount of mass to act as a heat sink. The new born has little ability to conserve heat by changing posture and no ability to adjust their own clothing in a response to thermal stress. To provide the similar environment as in the womb infants have to be kept in a device known as incubator. An infant incubator is a device consisting of a rigid box-like enclosure in which an infant may be kept in a controlled environment for medical care. An infant incubator provides stable levels of temperature, relative humidity and oxygen concentration The relative humidity should follow set values according to the number of incubation days. incubators can reduce the chance of germs and additional infection while a little one heals from an illness. Incubators also offer a protected space where it’s possible to monitor vitals 24/7 when your baby also needs multiple IVs for medication, fluids, etc